Comparative analysis of the incidence of Oropharyngeal cancer and Laryngeal cancer in the region of south-eastern Poland from 1980 to 2013 - Gawełko, Jan; Cierpiał-Wolan, Marek; Kawecki, Andrzej; Podgórska-Bednarz, Justyna (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The incidence of head and neck cancers in Poland demonstrated a general tendency to stabilize in the last two decades. However, a global phenomenon in the change of morbidity structure in terms of the specific anatomical location is observed, which will probably increasingly apply also to Poland. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to present the changes that have occurred in the structure of the incidence of oropharyngeal cancer in comparison to laryngeal cancer in the period from 1980 to 2013, in the region of south-eastern Poland and the whole country. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A retrospective analysis of the incidence due to the head and neck organ cancer in 1980-2013 in the region of south-eastern Poland and the whole country was performed based on demographic data from the Provincial Statistical Office in Rzeszow and Podkarpackie Cancer Register as well as the Department of Epidemiology, Oncology Centre in Warsaw. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results and conclusion. In the last three decades, the percentage of laryngeal cancer incidence in women (13% vs 18%) as well as oropharyngeal cancer (18.2 % vs 21.6%) was lower in Podkarpacie than in Poland overall. The incidence of oropharyngeal cancer in men in Podkarpacie was lower in the analyzed period than in Poland overall, and only in the last 3 years of observation has it reached a value close to the average for the country. The incidence of laryngeal cancer in men showed a dramatic downward trend both in Poland and in the Podkarpacie province, whereby both in terms of incidence rates and standardized rates and percentages – it is far more pronounced in the analyzed province.